Peningkatan pemahaman konsep hak dan kewajiban menggunakan model make a match pada siswa kelas IV sekolah dasar - Naimah Rahmawati (Universitas Sebelas Maret, 2020)
The purpose of this research is improve the understanding of the concept of rights and obligations with the use of models Make a Match. This research is a classroom action research (CAR). Subjects were fourth grade student primary school of Soropadan No. 108 Laweyan Surakarta totaling 30 students. Sources of data is teachers, students, teaching process, and document. Data collection techniques are observation, interviews, tests, and documentation. Analysis of data using interactive techniques for qualitative data analysis developed by Miles Huberman. Classical completeness in pre-action was 26,66%. Classical completeness then increased by 70,00% in cycle I, continued with the second cycle with the percentage of 63,33%, and continued with the thrid cycle with the percentage of 86,66%. The conclusions of this study is the use of models Make a Match improve the understanding of the concept of rights and obligations of fourth grade student primary school of Soropadan No. 108. contribution of the implementation of the make a match model is to be used as a reference, input and be a development in varied learning activities in the classroom, especially in PKn subject.